Investigation of contamination caused by rubber compactor in arsine purified in gas centrifuge; Bulletin of the Tomsk Polytechnic University; Vol. 310, № 1 - Zaykov А. А.; Zyryanov S. М.; Kulinich Yu. А.; Pulnikov I. I.; Skorynin G. М.; Vlasov V. А. (Chemistry, 2007)
Заглавие с титульного листа